Solid-state battery based on binder auxiliary agent modified PTFE and preparation method of solid-state battery

By using binder additive modified PTFE in solid-state batteries to prepare a fully conductive network, the problem of high resistivity of traditional solid-state batteries is solved, and higher ion migration capabilities and longer battery life are achieved.

CN119764523APending Publication Date: 2025-04-04YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411956843.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional solid-state batteries have high resistivity, which affects their performance and life, and the use of electrolyte increases complexity and cost.

Method used

By introducing the binder additive modified polytetrafluoroethylene (PTFE), a fully conductive solid electrolyte separator, an anode electrolyte mixed film and a positive electrode electrolyte mixed film are prepared to build a fully conductive network that penetrates the positive and negative electrodes.

Benefits of technology

It reduces the resistivity of solid-state batteries, improves ion migration capabilities, enhances charging and discharging efficiency, and improves the cycle life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a solid-state battery based on binder auxiliary agent modified PTFE, the solid-state battery comprises a full-conductive solid-state electrolyte diaphragm, a negative electrode electrolyte mixed membrane, a positive electrode electrolyte mixed membrane and a current collector, the raw materials of the full-conductive solid-state electrolyte diaphragm comprise modified PTFE and a solid-state electrolyte; the negative electrode electrolyte mixed membrane raw materials comprise modified PTFE, a negative electrode active material, a negative electrode conductive agent and a solid electrolyte; the positive electrode electrolyte mixed membrane comprises modified PTFE, a positive electrode active material, a positive electrode conductive agent and a solid electrolyte; the modified PTFE raw materials comprise a binder aid and PTFE, and the binder aid is selected from one or more of a polyacrylonitrile-styrene copolymer, a polyacrylic acid-styrene copolymer or polyurethane. According to the invention, the problem of high resistivity of the traditional solid-state battery is solved, and the solid-state battery based on the binder additive modified PTFE is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid-state batteries, and in particular relates to a solid-state battery based on binder-aid-modified PTFE and a preparation method thereof. Technical Background

[0002] Solid-state batteries are widely considered to be an important direction for the development of future battery technology due to their significant advantages in energy density and safety. Compared with traditional liquid batteries, solid-state batteries can provide higher energy storage capacity, which means that under the same volume or weight conditions, solid-state batteries can store more electrical energy, thereby extending the battery life and improving the operating efficiency of the equipment. In addition, the solid electrolyte of solid-state batteries greatly reduces the risk of leakage and thermal runaway, which makes them perform better in terms of safety, especially in applications under extreme conditions.

[0003] However, in the actual application of solid-state batteries, lithium ions and sodium ions must cross the interface between the positive electrode, the separator and the negative electrode. This process is one of the determining factors of solid-state battery performance. In order to assist lithium ions or sodium ions to effectively cross this interface, a small amount of electrolyte is usually introduced in the mainstream technical route. Although this electrolyte mixing method can reduce the resistance to ion migration to a certain extent, the use of electrolyte may increase the complexity and cost of the battery, and may also affect the stability and life of the battery under certain conditions. How to avoid the influence of electrolyte on the performance of solid-state batteries, optimize the interface characteristics of solid-state batteries, and reduce the resistivity of solid-state batteries has become a hot spot and difficulty in current research. Summary of the invention

[0004] The present invention aims at the problems in the prior art and provides a solid-state battery based on PTFE modified by a binder additive, which solves the problem of high resistivity of traditional solid-state batteries and obtains a solid-state battery with low resistivity.

[0005] In the first aspect, the present invention provides a solid-state battery based on PTFE modified by a binder additive, comprising a fully conductive solid electrolyte diaphragm, a negative electrode electrolyte mixed membrane, a positive electrode electrolyte mixed membrane and a current collector, wherein the raw materials of the fully conductive solid electrolyte diaphragm include modified PTFE and a solid electrolyte;

[0006] The raw materials of the negative electrode electrolyte mixed membrane include modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte;

[0007] The positive electrode electrolyte mixed membrane includes modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte;

[0008] The modified PTFE raw material comprises a binder auxiliary and polytetrafluoroethylene (PTFE), and the binder auxiliary is selected from one or more of polyacrylonitrile-styrene copolymer, polyacrylic acid-styrene copolymer or polyurethane.

[0009] As a further solution, in the modified PTFE raw material, the mass ratio of the binder additive to PTFE is selected from (1-10): (90-99).

[0010] As a further solution, the weight average molecular weight of the binder additive is selected from 50,000-1,000,000 g / mol.

[0011] As some preferred solutions, the weight average molecular weight of the binder additive is selected from 100,000-500,000 g / mol.

[0012] As a further solution, the solid electrolyte is selected from any one of an organic solid electrolyte and an inorganic solid electrolyte, wherein the organic solid electrolyte is selected from a polymer electrolyte.

[0013] As a further solution, the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0014] As a further solution, the mass ratio of the modified PTFE to the solid electrolyte is selected from (1-60): (99-1).

[0015] As a further solution, the mass ratio of the modified PTFE to the solid electrolyte is selected from (1-5): (95-99).

[0016] As a further solution, the negative electrode active material is selected from any one of graphite, silicon, lithium metal, lithium titanate, tin, carbon nanotubes, carbon nitride, manganese oxide, and zinc oxide.

[0017] As a further solution, the negative electrode conductive agent is selected from any one or more of carbon black, super carbon, graphite, graphene, carbon nanotubes, polyaniline, polypyrrole, nitrogen-doped graphene, activated carbon, and lithium titanate.

[0018] As a further solution, in the negative electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte is selected from the range of (1-10): (70-99): (1-10): (1-30).

[0019] As a further solution, in the negative electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte is selected from the range of (1-5): (90-95): (1-5): (5-10).

[0020] As a further embodiment, the positive electrode active material is selected from lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, sodium nickel iron manganese oxide, sodium iron pyrophosphate phosphate, sodium vanadium phosphate, lithium vanadium phosphate, nickel cobalt manganese oxide such as NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) any one or more.

[0021] As a further solution, the positive electrode conductive agent is selected from any one or more of carbon black, conductive carbon, Super P, graphene, carbon nanotubes, polyaniline, polypyrrole, conductive carbon black, nitrogen-doped graphene, activated carbon, and polyimide.

[0022] As a further solution, in the raw material of the positive electrode electrolyte mixed membrane, the mass ratio of modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte is selected from the range of (1-10): (70-99): (1-10): (1-30).

[0023] As a further solution, in the raw material of the positive electrode electrolyte mixed membrane, the mass ratio of modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte is selected from the range of (1-5): (90-95): (1-5): (5-10).

[0024] As a further solution, a metal foil is used as a current collector, and the current collector includes a positive electrode current collector and a negative electrode current collector.

[0025] As a further solution, the positive electrode current collector material is selected from any one of nickel and aluminum.

[0026] As a further solution, the negative electrode current collector material is selected from any one of copper, nickel, aluminum, and nickel-cobalt alloy.

[0027] In a second aspect, the present invention also provides a method for preparing a solid-state battery based on PTFE modified with a binder additive, comprising the following steps:

[0028] S1: mixing the solid electrolyte, the binder additive and the PTFE by dry mixing to obtain a fully conductive solid electrolyte diaphragm premix material;

[0029] S2: The fully conductive solid electrolyte membrane premix material is fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential rolling at 70-90° C., the roll gap is selected from 30-50 μm, the pressure is selected from 25-35t, and the fully conductive solid electrolyte membrane is obtained after thinning 2-4 times;

[0030] S3: mixing the solid electrolyte, the binder additive, PTFE, the negative electrode active material, and the negative electrode conductive agent by dry mixing to obtain a negative electrode electrolyte mixed membrane premix;

[0031] S4: The negative electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roller gap is selected from 150-170 μm, the pressure is selected from 25-35t, and the negative electrode electrolyte mixed membrane is obtained after thinning 2-4 times;

[0032] S5: Mixing the modified PTFE, the positive electrode active material, the positive electrode conductive agent, and the solid electrolyte by dry mixing and stirring to obtain a positive electrode electrolyte mixed membrane premix;

[0033] S6: The positive electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roll gap is selected from 180-220 μm, the pressure is selected from 25-35t, and the positive electrode electrolyte mixed membrane is obtained after thinning 2-4 times;

[0034] S7: Compound the negative electrode electrolyte mixed membrane with the negative electrode current collector to obtain a negative electrode sheet, compound the positive electrode electrolyte mixed membrane with the positive electrode current collector to obtain a positive electrode sheet, stack the negative electrode sheet, the separator, and the positive electrode sheet 10 times in the order of negative electrode sheet / separator / positive electrode sheet, and prepare a solid-state battery based on binder auxiliary modified PTFE by thermal compounding, welding, packaging, and chemical formation.

[0035] As a further solution, the sieve used in steps S2, S4, and S6 is selected from 50-70 mesh.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects:

[0037] This scheme successfully achieves the modification of PTFE by introducing various polymers such as polyacrylonitrile-styrene copolymer, polyacrylic acid-styrene copolymer or polyurethane into polytetrafluoroethylene. The introduction of these polymers not only improves the bonding properties of PTFE, but also retains its excellent chemical stability and electrical insulation properties. On this basis, the modified PTFE, solid electrolyte and positive and negative electrode active materials are combined to prepare a fully conductive solid electrolyte diaphragm, a negative electrode electrolyte mixed membrane and a positive electrode electrolyte mixed membrane. Through the fully conductive solid electrolyte diaphragm, negative electrode electrolyte mixed membrane and positive electrode electrolyte mixed membrane prepared by the present invention, the present invention successfully constructs a fully conductive network that runs through the positive and negative electrodes. This network not only effectively enhances the migration ability of ions in solid-state batteries, but also reduces the resistance inside the battery and improves the charge and discharge efficiency of the battery. In addition, the use of modified PTFE makes the overall structure more stable, improves the cycle life and safety of the battery, and further enhances the overall performance of the battery. DETAILED DESCRIPTION

[0038] For ease of understanding, a solid-state battery based on binder-aid-modified PTFE will be described in more detail below, and examples of the present invention will be given, but the scope of the present invention is not limited thereby.

[0039] In the first aspect, the present invention provides a solid-state battery based on PTFE modified by a binder additive, comprising a fully conductive solid electrolyte diaphragm, a negative electrode electrolyte mixed membrane, a positive electrode electrolyte mixed membrane and a current collector, wherein the raw materials of the fully conductive solid electrolyte diaphragm include modified PTFE and a solid electrolyte;

[0040] The raw materials of the negative electrode electrolyte mixed membrane include modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte;

[0041] The positive electrode electrolyte mixed membrane includes modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte;

[0042] The modified PTFE raw material comprises a binder auxiliary and PTFE, wherein the binder auxiliary is selected from one or more of polyacrylonitrile-styrene copolymer, polyacrylic acid-styrene copolymer or polyurethane.

[0043] PTFE, as a polymer material with excellent chemical stability and electrical insulation properties, has been widely used as an electrolyte, diaphragm, and adhesive for solid-state batteries in recent years. However, PTFE itself has weak adhesion. Therefore, in the present invention, by introducing one or more polymers of polyacrylonitrile-styrene copolymer, polyacrylic acid-styrene copolymer or polyurethane, while retaining the good mechanical properties and pressure resistance of PTFE, the good performance of the adhesive auxiliary agent in cross-linking is utilized to further optimize the adhesion of PTFE, so that it can form a three-dimensional conductive network in combination with the solid electrolyte, thereby improving the stability and overall performance of the conductive network; this scheme prepares a fully conductive solid electrolyte diaphragm, a negative electrode electrolyte mixed membrane, and a positive electrode electrolyte mixed membrane by combining the modified PTFT with positive and negative electrode active materials and solid electrolytes, and uses the fully conductive solid electrolyte diaphragm as a battery diaphragm, combines the negative electrode electrolyte mixed membrane with the negative electrode collector as a battery negative electrode sheet, and combines the positive electrode electrolyte mixed membrane with the positive electrode collector as a battery positive electrode sheet, thereby constructing a fully conductive network that runs through the positive and negative electrodes in the solid-state battery, thereby effectively improving the ion migration capacity in the solid-state battery.

[0044] As examples of some optional parameters, in the modified PTFE raw material, the mass ratio of the binder additive to PTFE is selected from (1-10): (90-99).

[0045] As examples of some optional parameters, the weight average molecular weight of the binder additive is selected from 50,000-1,000,000 g / mol.

[0046] As a preferred example of some optional parameters, the weight average molecular weight of the binder additive is selected from 100,000-500,000 g / mol.

[0047] As examples of some optional parameters, the solid electrolyte is selected from any one of an organic solid electrolyte and an inorganic solid electrolyte, wherein the organic solid electrolyte is selected from a polymer electrolyte.

[0048] As examples of some optional parameters, the polymer electrolyte is selected from any one or more of polyethylene oxide, polyacrylonitrile, polyurethane, polystyrene sulfonic acid, polymethyl methacrylate, polyvinyl alcohol, polystyrene, polyether, polyamide, and polyisobutylene.

[0049] As examples of some optional parameters, the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0050] As examples of some optional parameters, the oxide solid electrolyte is selected from perovskite-type solid electrolytes such as LLTO (lithium lanthanum titanium oxide), garnet-type solid electrolytes such as LLZO (lithium lanthanum zirconium oxide), and NASICON-type solid electrolytes such as LATP (lithium aluminum titanium phosphate), etc.

[0051] As examples of some optional parameters, the sulfide solid electrolyte is selected from any one or more of lithium sulfide, sodium sulfide, cadmium sulfide, manganese sulfide, cobalt sulfide, aluminum sulfide, Li3PS4, and Li6PS5Cl.

[0052] As examples of some optional parameters, the halide solid electrolyte is selected from any one or more of lithium fluoride, lithium chloride, lithium bromide, sodium fluoride, sodium chloride, sodium bromide, calcium fluoride, aluminum fluoride, calcium chloride, and magnesium fluoride.

[0053] As examples of some optional parameters, the mass ratio of the modified PTFE to the solid electrolyte is selected from (1-60): (1-99).

[0054] As examples of some optional parameters, the mass ratio of the modified PTFE to the solid electrolyte is selected from (1-5): (95-99).

[0055] As examples of some optional parameters, the negative electrode active material is selected from any one of graphite, silicon, lithium metal, lithium titanate, tin, carbon nanotubes, carbon nitride, manganese oxide, and zinc oxide.

[0056] As examples of some optional parameters, the negative electrode conductive agent is selected from any one or more of carbon black, super carbon, graphite, graphene, carbon nanotubes, polyaniline, polypyrrole, nitrogen-doped graphene, activated carbon, and lithium titanate.

[0057] As examples of some optional parameters, in the negative electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte is selected from the range of (1-10): (70-99): (1-10): (1-30).

[0058] As examples of some optional parameters, in the negative electrode electrolyte mixed membrane raw material, the mass ratio range of modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte is selected from (1-5): (90-95): (1-5): (5-10).

[0059] As examples of some optional parameters, the positive electrode active material is selected from lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, sodium nickel iron manganese oxide, sodium iron pyrophosphate phosphate, sodium vanadium phosphate, lithium vanadium phosphate, nickel cobalt manganese oxide such as NCM811 (LiNi 0.8 Co 0.1 Mn 0.1O2) any one or more.

[0060] As examples of some optional parameters, the positive electrode conductor is selected from any one or more of carbon black, conductive carbon, Super P, graphene, carbon nanotubes, polyaniline, polypyrrole, conductive carbon black, nitrogen-doped graphene, activated carbon, and polyimide.

[0061] As examples of some optional parameters, in the positive electrode electrolyte mixed membrane raw material, the mass ratio range of modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte is selected from (1-10): (70-99): (1-10): (1-30).

[0062] As examples of some optional parameters, in the raw materials of the positive electrode electrolyte mixed membrane, the mass ratio of modified PTFE, positive electrode active material, positive electrode conductive agent, and solid electrolyte is selected from (1-5): (90-95): (1-5): (5-10). The modified PTFE, positive electrode active material, positive electrode conductive agent, and solid electrolyte selected from the above range are helpful to cooperate with the fully conductive solid electrolyte separator and the negative electrode electrolyte mixed membrane to build a more stable and uniform three-dimensional conductive network, thereby optimizing the electrochemical performance of the solid-state battery based on the binder-adjuvant modified PTFE.

[0063] As examples of some optional parameters, metal foil is used as the current collector, and the current collector includes a positive electrode current collector and a negative electrode current collector.

[0064] As examples of some optional parameters, the positive electrode current collector material is selected from any one of nickel and aluminum.

[0065] As examples of some optional parameters, the negative electrode current collector material is selected from any one of copper, nickel, aluminum, and nickel-cobalt alloy.

[0066] As examples of some optional parameters, the solid-state battery based on binder-aid-modified PTFE is not limited in principle, and can be selected from any one of lithium batteries and sodium batteries, for example.

[0067] In a second aspect, the present invention also provides a method for preparing a solid-state battery based on PTFE modified with a binder additive, comprising the following steps:

[0068] S1: mixing the solid electrolyte, the binder additive and the PTFE by dry mixing to obtain a fully conductive solid electrolyte diaphragm premix material;

[0069] S2: The fully conductive solid electrolyte membrane premix material is fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential rolling at 70-90° C., the roll gap is selected from 30-50 μm, the pressure is selected from 25-35t, and the fully conductive solid electrolyte membrane is obtained after thinning 2-4 times;

[0070] S3: mixing the solid electrolyte, the binder additive, PTFE, the negative electrode active material, and the negative electrode conductive agent by dry mixing to obtain a negative electrode electrolyte mixed membrane premix;

[0071] S4: The negative electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roller gap is selected from 150-170 μm, the pressure is selected from 25-35t, and the negative electrode electrolyte mixed membrane is obtained after thinning 2-4 times;

[0072] S5: Mixing the modified PTFE, the positive electrode active material, the positive electrode conductive agent, and the solid electrolyte by dry mixing and stirring to obtain a positive electrode electrolyte mixed membrane premix;

[0073] S6: The positive electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roll gap is selected from 180-220 μm, the pressure is selected from 25-35t, and the positive electrode electrolyte mixed membrane is obtained after thinning 2-4 times;

[0074] S7: Compound the negative electrode electrolyte mixed membrane with the negative electrode current collector to obtain a negative electrode sheet, compound the positive electrode electrolyte mixed membrane with the positive electrode current collector to obtain a positive electrode sheet, stack the negative electrode sheet, the separator, and the positive electrode sheet 10 times in the order of negative electrode sheet / separator / positive electrode sheet, and prepare a solid-state battery based on binder auxiliary modified PTFE by thermal compounding, welding, packaging, and chemical formation.

[0075] As examples of some optional parameters, the conditions for dry mixing and stirring in step S1 are generally not limited, and technicians can select different dry mixing and stirring conditions according to needs.

[0076] As examples of some optional parameters, the sieve used in steps S2, S4, and S6 is selected from 50 mesh to 70 mesh.

[0077] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0078] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0079] Example 1

[0080] S1: Polyurethane, PTFE and LATP were mixed evenly in a mass ratio of 0.05:0.95:99, and then fiberized at 80°C, with a fiberization speed of 20,000 rpm / min and a fiberization time of 5 min. After fiberization, the mixture was passed through a 60-mesh screen, and then high-pressure differential rolling was performed at an extrusion temperature of 80°C, with a roll gap of 40 μm and a pressure of 30 t. After the axial pressing, the mixture was thinned twice to prepare a fully conductive solid electrolyte membrane with a thickness of 20 μm.

[0081] S2: Polyurethane, PTFE, LATP, graphite, and conductive carbon black were mixed evenly in a mass ratio of 0.05:0.95:10:87:2, and fiberized at 80°C for 5 min at a fiberization speed of 20,000 rpm / min. After fiberization, the mixture was passed through a 60-mesh screen. Subsequently, high-pressure differential roller pressing was performed at an extrusion temperature of 80°C, with a roller gap of 160 μm and a pressure of 30 t. After the axial pressing, the mixture was thinned twice to prepare a negative electrode electrolyte mixed membrane with a thickness of 90 μm.

[0082] S3: Polyurethane, PTFE, LATP, NCM811, and conductive carbon black were mixed evenly in a mass ratio of 0.05:0.95:10:87:2, and fiberized at 80°C for 5 minutes at a fiberization speed of 20,000 rpm / min. After fiberization, the mixture was passed through a 60-mesh sieve. Subsequently, high-pressure differential rolling was performed at an extrusion temperature of 80°C, with a roll gap of 200 μm and a pressure of 30 t. After the axial pressing, the mixture was thinned twice to prepare a positive electrode electrolyte mixed membrane with a thickness of 100 μm.

[0083] S4: The positive electrode sheet is prepared by compounding the positive electrode electrolyte mixed film with 12 μm aluminum foil;

[0084] The negative electrode electrolyte mixed film is compounded with 6μm copper foil to obtain the negative electrode sheet; the positive electrode sheet, the negative electrode sheet and the separator are stacked 10 times in the order of negative electrode sheet / separator / positive electrode sheet, and the solid-state lithium-ion battery with a fully conductive network is prepared by thermal compounding, welding, packaging and chemical formation. The fully conductive solid electrolyte separator has a fracture elongation of 30% and a tensile strength of 130Mpa.

[0085] Example 2

[0086] The synthesis method and preparation steps are the same as those in Example 1, except that when preparing the fully conductive solid electrolyte membrane, the mass ratio of modified PTFE to solid electrolyte is 1:1, wherein the fully conductive solid electrolyte membrane has a fracture elongation of 100% and a tensile strength of 90 MPa.

[0087] Example 3

[0088] The synthesis method and preparation steps are the same as those in Example 1, except that when preparing the positive electrode electrolyte mixed membrane, the mass ratio of modified PTFE, solid electrolyte, positive electrode active material, and positive electrode conductive agent in the positive electrode electrolyte mixed membrane is 3:5:90:2, wherein the fracture elongation of the fully conductive solid electrolyte membrane is 31%, and the tensile strength is 131 MPa.

[0089] Example 4

[0090] The synthesis method and preparation steps are the same as those in Example 1, except that the mass ratio of modified PTFE, solid electrolyte, negative electrode active material, and negative electrode conductive agent in the preparation of the negative electrode electrolyte mixed membrane is 3:5:90:2, wherein the fracture elongation of the fully conductive solid electrolyte membrane is 30.8%, and the tensile strength is 130Mpa.

[0091] Comparative Example 1

[0092] PTFE is used as a separator, graphite is used as a negative electrode active material, conductive carbon black is used as a negative electrode conductive agent, a 6μm copper foil is used as a negative electrode current collector, NCM811 is used as a positive electrode active material, conductive carbon black is used as a positive electrode conductive agent, and a 12μm aluminum foil is used as a positive electrode current collector to prepare positive electrode sheets and negative electrode sheets. The positive electrode sheets, negative electrode sheets and separators are stacked 10 times in the order of negative electrode sheets / separator / positive electrode sheets, and a lithium-ion battery is prepared by thermal compounding, welding, packaging and chemical formation.

[0093] Comparative Example 2

[0094] The synthesis method and preparation steps are the same as those in Example 1, except that PTFE is used to replace the fully conductive solid electrolyte membrane.

[0095] Comparative Example 3

[0096] The synthesis method and preparation steps are the same as those in Example 1, except that NCM811 is used as the positive electrode active material, conductive carbon black is used as the positive electrode conductive agent, and 12 μm aluminum foil is used as the positive electrode current collector to prepare the positive electrode sheet and assemble it.

[0097] Comparative Example 4

[0098] The synthesis method and preparation steps are the same as those in Example 1, except that graphite is used as the negative electrode active material, conductive carbon black is used as the negative electrode conductive agent, and 6 μm copper foil is used as the negative electrode current collector to prepare the negative electrode sheet and assemble it.

[0099] The specific parameters of the embodiments and comparative examples are shown in Table 1, and the test results of the embodiments and comparative examples are shown in Table 2.

[0100] Table 1

[0101]

[0102]

[0103] Table 2

[0104] Case Ionic resistivity (Ω*cm) Example 1 <![CDATA[2.1*10 -2 ]]> Example 2 <![CDATA[2.26*10 -2 ]]> Example 3 <![CDATA[1.92*10 -2 ]]> Example 4 <![CDATA[1.94*10 -2 ]]> Comparative Example 1 <![CDATA[4.7*10 -1 ]]> Comparative Example 2 <![CDATA[6.54*10 -2 ]]> Comparative Example 3 <![CDATA[5.32*10 -2 ]]> Comparative Example 4 <![CDATA[5.47*10 -2 ]]>

[0105] It can be observed from Examples 1-4 and Comparative Examples 1-4 that Examples 1-4 exhibit better ionic resistivity than Comparative Examples 1-4, indicating that the solid-state battery with a fully conductive network proposed in this scheme can combine the positive and negative electrodes and the separator to construct a fully conductive network covering the positive and negative electrodes of the battery, thereby optimizing the ionic resistivity of the solid-state battery with a fully conductive network.

[0106] From Example 1 and Comparative Example 1, it can be observed that when the battery is prepared without using the fully conductive solid electrolyte membrane, the negative electrode electrolyte mixed membrane, and the positive electrode electrolyte mixed membrane proposed in this scheme, Comparative Example 1 exhibits an ionic resistivity much higher than that of Example 1, indicating that the solid-state battery based on binder-aid-modified PTFE proposed in this scheme can effectively reduce the battery resistivity, thereby optimizing the battery performance.

[0107] It can be observed from Example 1 and Comparative Examples 2-4 that in the solid-state battery based on binder-modified PTFE, the presence of a fully conductive solid electrolyte membrane, a negative electrode electrolyte mixed membrane, and a positive electrode electrolyte mixed membrane are all indispensable. This may be because no matter which part of the fully conductive solid electrolyte membrane, the negative electrode electrolyte mixed membrane, and the positive electrode electrolyte mixed membrane is present, a complete fully conductive network cannot be constructed in the solid-state battery, thereby affecting the performance of the solid-state battery. Therefore, it can be observed from Example 1 and Comparative Examples 2-4 that Comparative Examples 2-4 exhibit an ionic conductivity much higher than that of Example 1.

[0108] The presence of modified PTFE helps to build a conductive network in combination with a solid electrolyte. In Examples 1-2, we can observe that Example 1 has a better ionic resistivity than Example 2. This may be because when the mass ratio of modified PTFE to solid electrolyte is selected from (1-5): (95-99), it helps to build a more stable and uniform three-dimensional conductive network, thereby optimizing the ionic resistivity of Example 2.

[0109] It can be observed from Examples 1, 3-4 that, compared with Example 1, Examples 3 and 4 exhibit better ionic resistivity. This may be because when the mass ratio of modified PTFE, solid electrolyte, positive electrode active material, and positive electrode conductive agent in the positive electrode electrolyte mixed membrane raw material is selected from (1-5): (5-10): (90-95): (1-5), and the mass ratio of modified PTFE, solid electrolyte, negative electrode active material, and negative electrode conductive agent in the negative electrode electrolyte mixed membrane is selected from (1-5): (5-10): (90-95): (1-5), it is helpful to combine the fully conductive solid electrolyte membrane to build a more uniform conductive network. Therefore, Examples 3 and 4 show better ionic conductivity than Example 1.

[0110] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A solid-state battery based on PTFE modified with a binder additive, characterized in that: It includes a fully conductive solid electrolyte diaphragm, a negative electrode electrolyte mixed membrane, a positive electrode electrolyte mixed membrane and a current collector, wherein the raw materials of the fully conductive solid electrolyte diaphragm include modified PTFE and a solid electrolyte; The raw materials of the negative electrode electrolyte mixed membrane include modified PTFE, negative electrode active material, negative electrode conductive agent, and solid electrolyte; The positive electrode electrolyte mixed membrane includes modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte; The modified PTFE raw material comprises a binder auxiliary and PTFE, wherein the binder auxiliary is selected from one or more of polyacrylonitrile-styrene copolymer, polyacrylic acid-styrene copolymer or polyurethane.

2. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: In the modified PTFE raw material, the mass ratio of the binder additive to the PTFE is selected from (1-10): (90-99); Preferably, the weight average molecular weight of the binder additive is selected from 50000-1000000 g / mol; Preferably, the weight average molecular weight of the binder additive is selected from 100000-500000 g / mol; Preferably, the solid electrolyte is selected from any one of an organic solid electrolyte and an inorganic solid electrolyte, wherein the organic solid electrolyte is selected from a polymer electrolyte; Preferably, the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

3. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: The mass ratio of the modified PTFE to the solid electrolyte is selected from (1-60): (1-99); Preferably, the mass ratio of the modified PTFE to the solid electrolyte is selected from (1-5): (95-99).

4. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: The negative electrode active material is selected from any one of graphite, silicon, lithium metal, lithium titanate, tin, carbon nanotubes, carbon nitride, manganese oxide, and zinc oxide; Preferably, the negative electrode conductive agent is selected from any one or more of carbon black, super carbon, graphite, graphene, carbon nanotubes, polyaniline, polypyrrole, nitrogen-doped graphene, activated carbon, and lithium titanate.

5. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: In the negative electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, negative electrode active material, negative electrode conductive agent and solid electrolyte is selected from the range of (1-10): (70-99): (1-10): (1-30); Preferably, in the negative electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, negative electrode active material, negative electrode conductive agent and solid electrolyte is selected from the range of (1-5): (90-95): (1-5): (5-10).

6. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: The positive electrode active material is selected from lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, sodium nickel iron manganese oxide, sodium iron pyrophosphate, sodium vanadium phosphate, lithium vanadium phosphate, nickel cobalt manganese oxide such as NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2) any one or more; Preferably, the positive electrode conductive agent is selected from any one or more of carbon black, conductive carbon, Super P, graphene, carbon nanotubes, polyaniline, polypyrrole, conductive carbon black, nitrogen-doped graphene, activated carbon, and polyimide.

7. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: In the positive electrode electrolyte mixed membrane raw material, the mass ratio of modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte is selected from the range of (1-10): (70-99): (1-10): (1-30); Preferably, in the raw material of the positive electrode electrolyte mixed membrane, the mass ratio of modified PTFE, positive electrode active material, positive electrode conductive agent and solid electrolyte is selected from the range of (1-5): (90-95): (1-5): (5-10).

8. The solid-state battery based on PTFE modified with a binder additive according to claim 1, characterized in that: A metal foil is used as a current collector, wherein the current collector includes a positive electrode current collector and a negative electrode current collector; Preferably, the positive electrode current collector material is selected from any one of nickel and aluminum; Preferably, the negative electrode current collector material is selected from any one of copper, nickel, aluminum, and nickel-cobalt alloy.

9. A method for preparing a solid-state battery based on PTFE modified with a binder additive, characterized in that: The method comprises the following steps: S1: mixing a solid electrolyte, a binder additive and PTFE by dry mixing and stirring to obtain a fully conductive solid electrolyte diaphragm premix material; S2: The fully conductive solid electrolyte membrane premix material is fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential rolling at 70-90° C., the roll gap is selected from 30-50 μm, the pressure is selected from 25-35t, and the fully conductive solid electrolyte membrane is obtained after thinning 2-4 times; S3: mixing the solid electrolyte, the binder additive, PTFE, the negative electrode active material, and the negative electrode conductive agent by dry mixing to obtain a negative electrode electrolyte mixed membrane premix; S4: The negative electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roller gap is selected from 150-170 μm, the pressure is selected from 25-35t, and the negative electrode electrolyte mixed membrane is obtained after thinning 2-4 times; S5: Mixing the modified PTFE, the positive electrode active material, the positive electrode conductive agent, and the solid electrolyte by dry mixing and stirring to obtain a positive electrode electrolyte mixed membrane premix; S6: The positive electrode electrolyte mixed membrane premix is ​​fiberized at a temperature of 70-90° C. for 3-8 min, the fiberization speed is selected from 18000-21000 rpm / min, sieved after the fiberization, and subjected to high-pressure differential speed rolling at 70-90° C., the roll gap is selected from 180-220 μm, the pressure is selected from 25-35t, and the positive electrode electrolyte mixed membrane is obtained after thinning 2-4 times; S7: Compound the negative electrode electrolyte mixed membrane with the negative electrode current collector to obtain a negative electrode sheet, compound the positive electrode electrolyte mixed membrane with the positive electrode current collector to obtain a positive electrode sheet, stack the negative electrode sheet, the separator, and the positive electrode sheet 10 times in the order of negative electrode sheet / separator / positive electrode sheet, and prepare a solid-state battery based on binder auxiliary modified PTFE by thermal compounding, welding, packaging, and chemical formation.

10. The method for preparing a solid-state battery based on PTFE modified with a binder additive according to claim 9, characterized in that: The sieve used in steps S2, S4 and S6 is selected from 50-70 mesh.